Association between common polymorphisms in ERCC gene and glioma risk: A meta-analysis of 15 studies. Issue 20 (May 2017) - Qian, Tengda; Zhang, Bin; Qian, Chunsheng; He, Yunwen; Li, Yihuan
Abstract: Background: A number of studies have investigated the roles of excision repair cross complementation group 1 (ERCC1), ERCC2, and ERCC5 genes polymorphisms in the development of glioma; however, the results were inconsistent. Here, we performed a meta-analysis to investigate the association between 6 polymorphisms in the ERCC genes (rs3212986, rs11615, rs13181, rs1799793, rs238406, rs17655) and glioma risk. Methods: The PubMed, Embase, and Web of science were searched up to September 6, 2016, for studies on the association between ERCC polymorphisms and glioma risk. A fixed-effects or random-effects model was used to calculate the pooled odds ratios based on the results from the heterogeneity tests. Sensitivity and cumulative meta-analyses were also performed. Results: A total of 15 studies were eligible for the pooled analysis, conducted in 2 populations of ethnic descent: 8 Europeans and 7 Asians. The results showed that ERCC1 rs3212986 polymorphism was positively associated with glioma [AA vs CC: odds ratio (OR) = 1.298, 95% confidence interval (95% CI) = 1.043–1.230, P = .025]. Association of the ERCC2 rs13181 and rs1799793 polymorphisms was only observed in Asians (CC vs AA for rs13181: OR = 1.539, 95% CI = 1.122–2.109, P = .007; AA vs GG for rs1799793: OR = 1.474, 95% CI = 1.090–1.994, P = .012). However, no association was observed between glioma risk and ERCC1 rs11615, ERCC2 rs238406, and ERCC5 rs17655 polymorphisms. Moreover, sensitivity and cumulative meta-analyses confirmed the stability of the results. Conclusions: Our meta-analysis indicated that the ERCC1 rs3212986 polymorphism and 2 polymorphisms in ERCC2 gene (rs13181 and rs1799793) contributed to the susceptibility of glioma.